Consumer palatability scores, sensory descriptive attributes, and volatile compounds of grilled beef steaks from three USDA Quality Grades. (February 2016) - Legako, J.F.; Dinh, T.T.N.; Miller, M.F.; Adhikari, K.; Brooks, J.C.
Abstract: Consumer palatability scores, sensory descriptive attributes, and volatile compounds were assessed for beef Longissimus lumborum steaks of USDA Prime, Low Choice, and Standard grades. Overall and flavor liking was greater ( P < 0.05) for Prime and Low Choice. Initial flavor impact and fat-like attributes were greater ( P < 0.05) among Prime and Low Choice. Prime had greater ( P < 0.05) brown/roasted, beef identity, overall sweetness, and umami. Cardboard was greater ( P < 0.05) in Standard. Volatile compounds representing flavor development pathways were varied with quality grade. Standard had greater ( P < 0.05) abundances of n -aldehydes. Phenylacetaldehyde was greater ( P < 0.05) in Prime and Low Choice. Both 2, 3-butanedione and 3-hydroxy-2-butanone were greatest ( P < 0.05) in Prime. Overall liking was positively correlated with many descriptive attributes, 3-hydroxy-2-butanone, and phenylacetaldehyde, and negatively correlated with cardboard, green, and n -aldehydes. While the measured attributes and volatiles may not be causative of flavor, this data indicates potential for prediction of flavor through their measurement. Highlights: Beef consumer liking, descriptive attributes, and volatile compounds were explored. Consumers scored greater quality grades more highly. Descriptive attributes varied by quality grade. Volatile compounds were correlated with consumer overall liking and descriptive attributes. Results indicate the measured volatile compounds may be utilized as makers of flavor.